Assimilation of the Batak Angkola Language in Pintu Padang, North Sumatra, Indonesia - Nadra, Nadra; Marnita, Rina; Amini, Khofifah Aisyah (Jurnal Arbitrer, 2024)
The objective of this research is to describe the assimilation process in the Toba Batak language, specifically as it is spoken in Pintu Padang Village, located in North Sumatra, Indonesia. Assimilation is a type of sound change that is not the same to become the same or almost the same. This process can occur between segments in a word and between components in compound words. So, it is essential to formalize it by describing the sound features that undergo these changes. The data was gathered through observation and interviews. Listening to Batak Angkola speakers communicate with one another allowed for observations. Simultaneously, interviews were conducted by directly interviewing informants who were chosen based on particular criteria. Three individuals were interviewed using a structured interview format. In addition, a set of unstructured interviews was carried out with several other speakers. For this purpose, a generative phonology approach is used. Data analysis was carried out by the distributional method with the segmenting immediate constituents technique. After that, the distinctive features of the sound are explained. The results of this research show that assimilation took place in nasal consonants [m], [n], and [ŋ], which met the consonants [k], [p], [s], [t], [l], and [c]. The sounds [m], [n], and [ŋ] appear in the forms [p], [t] and [k], respectively. Then, the sound [n] appears in the form [l] and [c] when it meets the sounds [l] and [c] too. Generally, it can be inferred that sound modifications in the form of assimilation are homorganic.